1999
DOI: 10.1046/j.1439-0310.1999.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Brood Reduction in White Storks Mediated through Asymmetries in Plasma Testosterone Concentrations in Chicks

Abstract: We hypothesized that increasing chick plasma testosterone concentrations, transmitted from the mothers via their eggs, enhances survival of their offspring and that the fitness of the young, depending on the maternal hormones, is influenced by parental quality. To test our hypotheses we distinguished the broods of white storks Ciconia ciconia L. where chicks died and those where all chicks survived. We analysed the plasma testosterone concentrations in the chicks, the ability of the chicks to be first to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…In white storks (Ciconia ciconia), first hatched chicks are more aggressive, receive more food, and have higher plasma levels of testosterone than their siblings. The number of younger siblings that die is higher when the difference in testosterone levels between first and later hatched chicks is greater (Sasvári et al, 1999). Although the data are not based on experimental evidence, they suggest a role for testosterone in sibling competition and/or begging behavior.…”
Section: Introductionmentioning
confidence: 81%
“…In white storks (Ciconia ciconia), first hatched chicks are more aggressive, receive more food, and have higher plasma levels of testosterone than their siblings. The number of younger siblings that die is higher when the difference in testosterone levels between first and later hatched chicks is greater (Sasvári et al, 1999). Although the data are not based on experimental evidence, they suggest a role for testosterone in sibling competition and/or begging behavior.…”
Section: Introductionmentioning
confidence: 81%
“…The interest ing observation is that in some detailed studies on the W hite Stork breeding biology parental infanti cide was never observed. Infanticidal behaviour was not recorded during a three year study of the W hite Stork breeding at both low and high density (Sasvari et al 1999a(Sasvari et al , 1999b. Thus further detailed studies are necessary to explore the relationship betw een frequency of infanticide, parental quality and feeding conditions.…”
Section: Causes Of Parental Infanticidementioning
confidence: 99%
“…A new study of W hite Storks by Sasvari et al (1999a) has show n that one m aternal effect -the plasma testosterone concentrations in chicks, transm itted from the m others via their eggs -could have a remarkable influence on offspring survival. Sasvari et al (1999a) com pared broods of W hite Storks w here chicks died w ith those w here all chicks sur vived and analysed the plasma testosterone con centration in the chicks, their vigour and hatching order. It was found that highest testosterone levels w ere recorded in the first chick to hatch and the lowest in those chicks that hatched last.…”
Section: Brood Reduction and Parental Horm O Nal Favouritism In Whitementioning
confidence: 99%
“…Tortosa and Redondo (1992) observed that stork parents may kill their smaller chick, which, according to our findings, might be female. Sasvari et al (1999) also noted that cases of brood reduction were related to testosterone concentrations in chick blood. The first-hatched chicks, which had high plasma testosterone levels (hence mainly males although chicks were not sexed in the original study), responded faster to the feeding parent and received more food than did their younger siblings.…”
Section: Discussionmentioning
confidence: 91%